Do the best players "take-the-first"? Examining expertise differences in the option-generation and selection processes of young soccer players - Musculus, L. (Sport, Exercise, and Performance Psychology, 2018)
Expertise research in sports has established expert-novice differences in the decision-making of adults. Yet, little is known about whether expertise differences in decision making, that is, option generation and selection, are already evident in young players. To inform talent identification and development, this study investigated differences between young expert (n = 86) and near-expert soccer players (n = 83) regarding the option-generation and selection processes predicted by the Take-The-First (TTF) heuristic. Further, based on ecological rationality, the effect of time pressure on young players` option generation and selection was examined. Young players` (N = 169; Mage = 11.32, SDage = 1.77) option-generation and selection processes were assessed in a video-based soccer task using temporal occlusion. It was revealed that young expert players generated fewer options and selected the first as the best option more often than near-experts. This result underlines the importance of considering option generation when investigating expertise development. In addition, time pressure promoted the generation of fewer but better options and fostered the use of the Take-The-First heuristic. Thus, the present study highlights the ability of young players to adapt their decision strategy to the situation and theoretically extends decision-making research in sports by specifying the effect of time pressure. Further, practical implications for theory-based diagnostics and decision-making training are discussed.